This expression could be reordered as 1 + 3x + 2x2.
It is: 2(3x-7y) = 6x-14y
x(3x+6) or 3x(x+2). Id recomend the second one.
The three terms are 3x2, 7x and 1
x2 * -3x = -3x3
(3x + 2)(x + 5)
6x2+5x+1 = (3x+1)(2x+1) when factored
The highest power of the variable is 2, so it is a second degree polynomial.
y + 12 = -3(x - 2) y + 12 = -3x + 6 y = -3x - 6 or y = -3(x + 2)
The first equation factors to (3x + 2)(3x + 4) The second equation factors to (3a + 2b)(3a + 4b)
3x^2 + x + 2x^2 = 5x^2 + x
(3x)3 = 27x3 (We think the original form was simpler.)
3x3 - 3x2 + 2x - 2 = 3x2(x - 1) + 2(x - 1) = (3x2 + 2)(x - 1)
(x2 + 3x + 5)(x2 - 3x + 4)
If the original is 2x + 3x2 + 6 + 5x3, you should rearrange the terms in order of exponent:5x3 + 3x2 + 2x + 6
2x3 + 8x2 + 3x + 12 = (2x3 + 8x2) + (3x + 12) = 2x2(x + 4) + 3(x + 4) = (x + 4)(2x2 + 3) Since you have asked this question I am assuming that you are not yet at a level where you might want (2x2 + 3) factorised into its imaginary factors.
That can be factored to (3x - 5)(3x - 5) or (3x - 5)2
Let the symbol ^ mean "to the power" Then 9x^2 + 24x + 16 = (3x + 4)(3x +4) = (3x + 4)^2
3x2 - 15x + 42 = 3*(x2 - 5x + 14) which cannot be factorised further.
8x to the second power times 3x to the second power (8x)2 + (3x)2 = 64x2 + 9x2 = 73x2 is one possibility, except the problem called for multiplication which would make the answer 64x squared times 9x squared = 576x to the fourth power It could also be read this way: 8x squared times 3x squared equals 24x to the fourth power. I wish my computer would do those cool little twos.